2013
DOI: 10.1017/s0143814x13000032
|View full text |Cite
|
Sign up to set email alerts
|

Public sector reform and blame avoidance effects

Abstract: Blame avoidance has often been claimed to be an important rationale behind changes in the organisation of the public sector, but very few studies have examined whether and how public attribution of responsibility is actually affected by such reforms. For instance, how do changes in the formal allocation of authority affect public attribution of blame when things go wrong? Is the effect immediate or delayed? To advance our understanding of such questions, this paper presents an analysis of blame and credit attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 59 publications
(102 reference statements)
1
39
0
Order By: Relevance
“…On average, the negative articles outnumber the positive articles by 3:1. This level of negativity bias is quite similar to findings with respect to healthcare‐related news, where Mortensen (, p. 171) reports a 3:1 ratio in Denmark, and a 4:1 ratio in Norway (Mortensen , p. 237).…”
Section: Data and Research Designsupporting
confidence: 76%
“…On average, the negative articles outnumber the positive articles by 3:1. This level of negativity bias is quite similar to findings with respect to healthcare‐related news, where Mortensen (, p. 171) reports a 3:1 ratio in Denmark, and a 4:1 ratio in Norway (Mortensen , p. 237).…”
Section: Data and Research Designsupporting
confidence: 76%
“…Taken together, these deficits explain why implications regarding the consequences of BAB largely have to remain hypothetical and fragmentary. Scholars studying the topic are well aware of this: The claims that “[f]urther research should also examine the relation between the process and outcomes of blame games” (Boin et al., , p. 720) and that “it is worthwhile to open up the political systems and actually study blame and credit attribution within different political systems” (Mortensen, 2013a, p. 247) stress the need for comparative, context‐sensitive research.…”
Section: The Three Deficits Of Blame Avoidance Researchmentioning
confidence: 99%
“…Second, the political‐institutional context plays a major role in economic voting theory as well as in the work on political strategies: Economic voting theory has shown that the strength of the sanctioning behavior is a function of the political‐institutional setup (Anderson , 173‐4, ; Duch and Stevenson ; Rudolph , 204; van der Brug, van der Eijk, and Franklin ). Similarly, a number of contributions on political strategies have considered this contextual variable's implications on the viability and usefulness of political strategies like blame avoidance (Béland and Myles ; Green‐Pedersen ; Jensen and Mortensen ; Mortensen ; Wenzelburger ). Economic voting theory is therefore clearly applicable to policies and their electoral consequences (Giger and Nelson ; Tilley and Hobolt ).…”
Section: A Genealogy Of Political Strategy In Policy Analysismentioning
confidence: 99%